Online Resources to Support International Students' English Language Development : Final Report. - Miller, Julia; Miller, Joseph; Wilson, Kate (Office for Learning and Teaching, 2015)
Concern over the English language proficiency of international students in Australia means that there is a need for language support to help them increase their intercultural competency and communicate more effectively with lecturers and peers. Online resources can meet the needs of large numbers of students, but should be appealing and user-friendly. The proposed project will create a series of five videos and accompanying exercises to be placed on an existing, freely available website. These videos are innovative in their use of humour and their references to popular culture, with a central grammar detective character who solves language problems. Evaluation of the first resource in this series, created with an OLT seed fund grant, was overwhelmingly positive, and the proposed project will build on this success by addressing five new areas. The new materials have the potential to be placed on any Learning Management System and embedded into different disciplines, and are ideal for a flipped classroom approach.